Arguing with zombies : economics, politics, and the fight for a better future - Krugman, Paul R (W. W. Norton & Company, 2020)
"An accessible, compelling introduction to today's major policy issues from columnist, best-selling author, and Nobel Prize-winning economist Paul Krugman. There is no better guide than Paul Krugman to basic economics, the ideas that animate much of our public policy. Likewise, there is no better foe of zombie economics, the misunderstandings that just won't die. This delightful new book finds Krugman at his best, turning readers into intelligent consumers of the daily news with quick, vivid sketches of the key concepts behind taxes, health care, international trade, and more. Arguing with Zombies will put Krugman at the front of the debate in the 2020 election year. Building on and expanding his New York Times columns and other writings, it contains short, accessible chapters on topics including the fight for national health care in the United States, the housing bubble and financial meltdown of 2007- 2008, the European Union and Brexit, the attack on Social Security, and the fraudulent argument- the ultimate zombie- that tax cuts for the rich will benefit all"--